Visual Biases in Decision Making - Orquin, Jacob L; Perkovic, Sonja; Grunert, Klaus G (Review of agricultural economics, 2018)
We review research on eye movements in decision making and show that decision makers are subject to several visual biases such as the size, salience, position, emotional valence, predictability, and number of information elements. These biases lead decision makers to allocate their attention in ways that are arbitrary to their goals and sometimes bias their choices. We show that while some visual biases can be minimized, others are unavoidable. Consequently, it is impossible to present information in a completely neutral way. Any presentation format will bias decision makers to attend or ignore different information and thereby influence their choices.